2015
DOI: 10.1007/s11356-015-4167-6
|View full text |Cite
|
Sign up to set email alerts
|

Oil spill effects on macrofaunal communities and bioturbation of pristine marine sediments (Caleta Valdés, Patagonia, Argentina): experimental evidence of low resistance capacities of benthic systems without history of pollution

Abstract: The Patagonian coast is characterized by the existence of pristine ecosystems which may be particularly sensitive to oil contamination. In this study, a simulated oil spill at acute and chronic input levels was carried out to assess the effects of contamination on the macrobenthic community structure and the bioturbation activity of sediments sampled in Caleta Valdés creek. Superficial sediments were either noncontaminated or contaminated by Escalante crude oil and incubated in the laboratory for 30 days. Oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 91 publications
(90 reference statements)
0
24
0
Order By: Relevance
“…population -a decrease in fertility, a change in biomass, abundance, in particular, an abnormal "outbreak" of a species as an indicator of stability disturbances, changes in the sizeweight, sexual, generative and spatial structure, death of the least stable individuals in the population [8,10,11,28,31,32,[37][38][39][40][41][42][43][44][45][46][47][48];…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…population -a decrease in fertility, a change in biomass, abundance, in particular, an abnormal "outbreak" of a species as an indicator of stability disturbances, changes in the sizeweight, sexual, generative and spatial structure, death of the least stable individuals in the population [8,10,11,28,31,32,[37][38][39][40][41][42][43][44][45][46][47][48];…”
Section: Discussionmentioning
confidence: 99%
“…biocenotic -a change in the species, size and trophic structure, type of dominance, violation of interspecific relationships and interpopulation relations [5,8,9,11,25,38,[40][41][42][43][44][45][47][48][49][50][51];…”
Section: Discussionmentioning
confidence: 99%
“…Gilbert et al (2014) showed that the macrofaunal community structure was not affected by an oil contamination in a historically hydrocarbon-contaminated sediment but the sedimentreworking activity was characterized by a deeper particle burial. In contrast, Ferrando et al (2015) demonstrated the deleterious effect of crude oil on macrofaunal community structure and reworking activity in a pristine sediment without pollution history suggesting that macrofaunal species could serve as bioindicators of pollution. The paper by Louati et al (2014b) confirms the negative impact of PAHs on macrofaunal communities and further demonstrates the capacity of bioremediation strategies (biostimulation and/ or bioaugmentation) to mitigate the effects of PAHs on macrofauna diversity.…”
mentioning
confidence: 88%
“…One may therefore expect that the ex situ measurements quantified the maximum biological sediment transports. Such ex situ measurements with a natural benthic community have been widely used in the literature (Duport et al, 2007;Cuny et al, 2015;Ferrando et al, 2015). Although the absolute values must be interpreted with caution, the relative comparisons between the stages of mangrove development remain valid.…”
Section: Bioturbation Measurementmentioning
confidence: 99%
“…The presence and intensity of biodiffusive mixing and non-local transport may vary substantially according to the structure of the benthic communities (species richness, density, biomass, and biovolume; Sandnes et al, 2000;Duport et al, 2006;Gilbert et al, 2007;Majdi et al, 2014) which in turn depends on the environmental variables (temperature, organic matter or pollutant inputs, vegetation; Duport et al, 2007;Bernard et al, 2014;Cuny et al, 2015;Ferrando et al, 2015). Previous studies in ecology have shown that the productivity of an ecosystem is more dependent on its bioturbation functional richness than on its species richness (Solan et al, 2004;Mermillod-Blondin et al, 2005;Michaud et al, 2006;Norling et al, 2007).…”
Section: Introductionmentioning
confidence: 99%